Estimation of seismic attenuation from zero-offset VSP acquired in hard rock environments - Pevzner, Roman; Greenwood, Andrew; Urosevic, Milovan; Gurevich, Boris (CSIRO, 2013)
Understanding of seismic attenuation plays an important role in successful application of seismic imaging and subsurface characterisation techniques based on amplitude analysis. Zero-offset vertical seismic profiling (VSP) is one of the principal tools which can be used to study seismic attenuation. Apparent attenuation estimated from seismic data analyses comprises of scattering and intrinsic components. Scattering mechanism can play significant role in hard rock environments in areas associated with fracture zones or other complex structures. As such seismic attenuation can be an important seismic exploration attribute. Meanwhile attenuation analyses from VSP data are almost routinely done in oil and gas industry they are still uncommon in mineral exploration. In this study we analyse zero-offset VSP data acquired in Western Australia on one of CRC DET test sites using both hydrophones and 3C geophones as receivers. We compare several methods for apparent attenuation estimation and evaluate of their applicability to VSP data acquired in crystalline rocks. Extensive wire line log coverage for the well allows us to investigate relative contribution of different attenuation mechanisms.